Menumbuhkan Minat Siswa Dalam Pengembangan Diri Seni Tari Di SMA Negeri 1 Ulakan Tapakis Kabupaten Padang Pariaman (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
This article aims to foster students' interest in self-development which is carried out at SMA Negeri 1 Ulakan Tapakis in the field of dance. This research is a quantitative research with the object of research namely SMA Negeri 1 Ulakan Tapakis. The population is students of class X and XI SMA Negeri 1 Ulakan Tapakis. The sample in this study were students who were interested in participating in dance self-development activities totaling 14 female students. The research instrument was the researcher himself and was assisted by supporting instruments such as stationery and cellphone cameras. Data collection techniques are carried out by means of observation, interviews, and documentation. Data were analyzed using percentage formula. The results showed that there was a growth in student interest from the first meeting to the last meeting. The final data obtained from indicators of feeling happy were that 0 students (0%) were not happy, 2 students (14%) were happy, and 12 students (86%) were very happy. Respondents Achievement Level (TCR), an indicator of feeling happy, 59% is classified as moderate. Student interest, 0 students (0%) were not interested, 2 students (14%) were interested, and 12 students (86%) were very interested. Respondent Achievement Level (TCR), an indicator of student interest, 54% is classified as moderate. Attention students, no attention there are 0 students (0%), attention there are 3 students (21%), and very concerned there are 11 students (79%). Respondent Achievement Level (TCR) 54% student attention is classified as moderate. Student involvement, 0 students (0%) were not involved, 0 students (0%) were involved, and 14 students (100%) were very involved. Respondent Achievement Level (TCR) student involvement 53% is classified as moderate.